Identifikasi Menurunnya Tekanan Kompresi Pada Main Air Compressor Di MV Hijau Samudra - Farin Arfianto, Farin Arfianto; Prayogo, Darul; Yuntoro, Kresno (Indonesian Journal of Marine Engineering, 2025)
Main air compressor is an auxiliary tool for the ship's main engine that functions to produce compressed air. Compressed air is needed in ship machinery that supports the entire ship's operational system. Main air compressor has a vital role in the ship's motion process, therefore if there is a decrease in compression pressure which causes reduced productivity of compressed air produced by the main air compressor, of course, it will hamper the entire operational process on the ship. Factors causing the compression pressure in the main air compressor to decrease are leaks in the valve material, broken piston rings, and dirty air filters. This can occur due to negligence of maintenance on these components. The impact of the decrease in compression pressure on the main air compressor is the disruption of the entire ship's process because of the reduced supply of compressed air. Efforts that can be made to anticipate this can be done by doing routine cleaning of the valve spring with lapping techniques. Maintenance and checking of the main air compressor must be carried out in accordance with the SOP and manual book. If there is damage to the component and it is not suitable for use, it must be replaced immediately.